1997
DOI: 10.1063/1.869368
|View full text |Cite
|
Sign up to set email alerts
|

The linear evolution of centrifugal instabilities in curved, compressible mixing layers

Abstract: The linear development of Görtler vortices in a curved compressible mixing layer is studied. It has been shown both experimentally and theoretically that the curved mixing layer can support a centrifugal mode, which is believed to be similar to the Görtler vortex mode. This study follows the corresponding incompressible study of Otto, Jackson, and Hu, and attempts to demonstrate the effects compressibility has on the growth of such modes [J. Fluid Mech. 315, 85 (1996)]. The ultimate downstream fate of the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The two cases of a zero and a non-zero buoyancy parameter will be considered separately. The former case is relatively well understood, or at least when either curvature or buoyancy is present-the boundary layer experiencing the combined effects of curvature and buoyancy has not been studied in depth (with the exception of the inviscid theory of Stott and Denier [23]) but the effects are easily surmised from knowledge of both the individual problems [9,11,14] and the equivalent mixing layer problem [18][19][20]. The buoyancy-coupled boundary layer has received little attention in the literature and thus will be the main focus of attention here.…”
Section: Linear Resultsmentioning
confidence: 99%
“…The two cases of a zero and a non-zero buoyancy parameter will be considered separately. The former case is relatively well understood, or at least when either curvature or buoyancy is present-the boundary layer experiencing the combined effects of curvature and buoyancy has not been studied in depth (with the exception of the inviscid theory of Stott and Denier [23]) but the effects are easily surmised from knowledge of both the individual problems [9,11,14] and the equivalent mixing layer problem [18][19][20]. The buoyancy-coupled boundary layer has received little attention in the literature and thus will be the main focus of attention here.…”
Section: Linear Resultsmentioning
confidence: 99%
“…A theoretical investigation of the Görtler instability was later conducted by Owen et al ͑henceforth referred to as OSO͒ within a curved laminar compressible mixing-layer system. 5 OSO demonstrated that in a compressible mixing layer the centrifugal instabilities can also be observed for certain parameter regimes within the system for which the faster stream curves into a cooler slower stream. Such modes have no counterpart in the corresponding incompressible curved mixing-layer investigation by Otto et al, 6 and they were labeled as the "thermal modes."…”
Section: Introductionmentioning
confidence: 96%
“…It was also seen that a change in the initial perturbation only served to alter the base of the neutral curves and not the ultimate downstream behaviour. Owen, Seddougui & Otto (1997) completed a similar study to Hall (1982) (and also to the analytical part of Otto et al 1996) for a compressible mixing layer. As well as finding modes that have counterparts in the incompressible problem herein referred to as 'conventional modes', Owen et al (1997) found a new class of modes which do not exist in the incompressible problem; these 'thermal modes' arise when a significantly cooler and slower stream curves away from a faster stream (which is analogous to convex curvature).…”
Section: Introductionmentioning
confidence: 99%
“…Owen, Seddougui & Otto (1997) completed a similar study to Hall (1982) (and also to the analytical part of Otto et al 1996) for a compressible mixing layer. As well as finding modes that have counterparts in the incompressible problem herein referred to as 'conventional modes', Owen et al (1997) found a new class of modes which do not exist in the incompressible problem; these 'thermal modes' arise when a significantly cooler and slower stream curves away from a faster stream (which is analogous to convex curvature). It is worth noting that both of these classes of modes owe their existence to the presence of centrifugal force, the main difference being that the 'conventional modes' are driven by velocity shear, whereas the 'thermal modes' are sustained by thermal gradients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation